2004
DOI: 10.1016/s0967-0645(04)00059-1
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian surface circulation in the Gulf of California from a 3D numerical model

Abstract: The surface circulation of the Gulf of California was studied from a Lagrangian point of view using the results of a 3D numerical model. The advection of particles, whose depth is fixed, was carried out for annual and monthly periods with 710 particles homogeneously distributed over the gulf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The oceanography of the Gulf of California is extremely complex and local directions of water movement vary with season, thus it is difficult to make specific predictions. But several recent models of Gulf circulation predict that water masses are exchanged between upper and central Gulf gyres (Lavin and Marinone 2003;Makarov and Jiménez-Illescas 2003;Marinone 2003;Gutiérrez et al 2004) and it therefore seems likely that larvae who get offshore and into gyres could also disperse between regions.…”
Section: Contemporary Processes and Directions Of Larval Movementmentioning
confidence: 99%
“…The oceanography of the Gulf of California is extremely complex and local directions of water movement vary with season, thus it is difficult to make specific predictions. But several recent models of Gulf circulation predict that water masses are exchanged between upper and central Gulf gyres (Lavin and Marinone 2003;Makarov and Jiménez-Illescas 2003;Marinone 2003;Gutiérrez et al 2004) and it therefore seems likely that larvae who get offshore and into gyres could also disperse between regions.…”
Section: Contemporary Processes and Directions Of Larval Movementmentioning
confidence: 99%
“…The former study found that significant biological and environmental effects determine to where the larvae will disperse, while the latter showed that dispersal closely followed current patterns. In the Gulf of California, complex seasonal upwellings and various gyres have been shown to disperse particles (and likely gametes and larvae) both north and southward (Marinone 2003; Gutierrez et al 2004; Marinone et al 2009). As directionality of the currents change from a general southward flow in April to northward in June (Marinone et al 2009), the path that larvae in the Gulf of California take likely varies based upon the timing of the spawn and the directionality of the currents.…”
Section: Discussionmentioning
confidence: 99%
“…), a transition zone where different surface water masses converge and the distribution of horizontal and vertical water masses is affected by a number of seasonal and interannual processes (Castro et al ). The Gulf of California Water (GCW) has the highest salinity in the area (≥ 34.9) and a very variable temperature (> 12°C annual range), while the less salty (< 34.9) and relatively warmer Tropical Surface Water (TSW) enters from the Pacific Ocean (Beier ; Lavín and Marinone ; Gutiérrez et al ). The Subtropical Subsurface Water (SSW) is found beneath these surface waters (∼ 70 m depth) characterized by high dissolved inorganic carbon (> 2200 μmol kg −1 ), low temperature and little dissolved oxygen (Hernández‐Ayón et al ; Franco et al ) along with the California Current Water (CCW), which occurs seasonally and is characterized by cold temperature and low salinity levels, but is richer in oxygen than to the other three water masses just mentioned (Castro et al ).…”
Section: Methodsmentioning
confidence: 99%